Knowledge, Attitudes and Practices of Coping Mechanisms to Relieve Stress during the COVID-19 Pandemic among UAE Residents - Hamad, Shahd; Subeh, Hiyam; Barakat, Nebras; Momena, Daas; Alzarooni, Amal (International Journal of Psychology, 2025)
Purpose: Recent research studies conducted in the United Arab Emirates (UAE) showed that the Coronavirus disease 2019 (COVID-19) pandemic has had a significant detrimental psychological impact on the UAE population. Based on these outcomes, it is essential to investigate the knowledge, attitudes, and practices of the UAE population towards coping mechanisms. The purpose of this study is to investigate the knowledge, attitudes, and practices of the UAE residents towards coping mechanisms used to relieve stress during COVID-19 pandemic. Methodology: A cross-sectional study was conducted among UAE residents above the age of 18. A total of 292 participants were enrolled by volunteer sampling and data was collected using a self-administered questionnaire. The questionnaire included questions about demographics, prevalence, causes of stress, knowledge, attitudes, and practices of coping mechanisms. Practices were assessed using the Brief-COPE scale and the data collected was analyzed using the SPSS-26 program. Findings: Out of 292 participants, 213 (73%) were between 18-24 years old, 207 (71%) were females, 193 (66%) were Arabs, 222 (76%) were single, 199 (68%) were students, 169 (58%) had a bachelor’s degree or above, and 190 (65%) had an income ≤ 10,000 AED. 210 (71.9%) of the participants experienced varying levels of stress and the most common causes of stress were online learning and the health of family members. The level of knowledge about coping mechanisms was poor in 150 (51.4%) of participants. In the case of attitudes towards coping mechanisms, 173 (59.2%) and 183 (62.7%) of participants agreed that adaptive and maladaptive coping mechanisms were beneficial in relieving stress, respectively. The mean practices score for adaptive and maladaptive coping was 43.43/64 and 24.58/48, respectively. Unique Contribution to Theory, Practice and Policy: Stress management is vital for the overall well-being of the community. Awareness programs should be established to improve the perception and implementation of adaptive coping mechanisms among UAE population. Overall, the study emphasizes the urgent need for mental health awareness programs in the UAE to enhance adaptive coping mechanisms, reduce reliance on maladaptive strategies, and improve community resilience in future crises.